Water Poverty Indices of three rural communities in the southern Caribbean. Issue 3 (30th November 2021) - Stewart, Akilah; Seepersad, Catherine; Hosein, Aliya; Tripathi, Vrijesh; Mohammed, Azad; Agard, John; Cashman, Adrian; Chadee, Dave; Ramsubhag, Adesh
Abstract: The Caribbean region experiences significant water supply challenges, especially for 30% of the population who live in rural areas. Improved water resource management in this region would enhance water availability for its population, but this requires reliable quantitative data to guide relevant policy decisions. The Water Poverty Index (WPI) and its components can be valuable sources of such data but there has not been any recent calculation of this index for countries or communities in the Caribbean. In this study, the WPI was determined for three rural communities in the southern Caribbean: Carriacou, Grenada; Nariva, Trinidad and Tobago; and Speightstown, Barbados. Using data collected from 606 surveys of households as well as published statistics, the overall WPI scores were calculated to be 65/100 for Carriacou, 65/100 for Nariva and 70/100 for Speightstown, which all fell in the 'medium-low' and 'low' water poverty scale respectively. Resource and Use components had the lowest scores and thus require urgent attention. There were no statistically significant differences across the major components, which demonstrates the common water-related challenges in these Small Island Developing States, despite geographical diversity. This research will aid in defining national water resource management policies in rural communities of the Caribbean. HIGHLIGHTS: WPIs were calculated to be 65 for Carriacou, Grenada, 65 for Nariva, Trinidad and 70 for Speightstown, Barbados. The Resource component had the lowest scores. Residents' water use practices afforded some resilience to the water supply in Carriacou. A higher water per capita in Nariva did not equate to a higher WPI. Improving water storage and rainwater harvesting can enhance water resilience in the region. Graphical Abstract